2021
DOI: 10.3390/ani11082299
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Body Chemical Composition and Reproductive Traits in Rabbit Does

Abstract: The relationship among live weight, chemical body composition and energy content (at artificial insemination (AI) and three days before parturition), estimated by bioelectrical impedance with fertility rates and the percentage of kits born alive, was studied during the first three AI. The first AI was conducted at 16 weeks of age in 137 rabbit does that weighted 3.91 ± 0.46 kg. Their body chemical composition was 17.4 ± 0.50%, 16.1 ± 2.6%, 1067 ± 219 kJ/100 g body weight, for protein, fat and energy, respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 49 publications
(90 reference statements)
0
1
0
Order By: Relevance
“…In addition, the rabbit does that had a high PFT at the first AI showed a PFT evolution pattern different from the rest of the females until the second parturition, not being able to recover the body condition that they had at the time of the first parturition (Martińez-Paredes et al, 2019). In contrast, the body composition (body protein, fat and energy estimated by bioelectrical impedance) at first AI did not influence the fertility rate at the first parturition, but did so at the second one (Taghouti et al, 2021). These authors reported that the increase in body protein and fat combined with a low body protein/energy ratio at first AI improved the fertility rate at the second parturition.…”
Section: Rearing Development and Body Statusmentioning
confidence: 80%
“…In addition, the rabbit does that had a high PFT at the first AI showed a PFT evolution pattern different from the rest of the females until the second parturition, not being able to recover the body condition that they had at the time of the first parturition (Martińez-Paredes et al, 2019). In contrast, the body composition (body protein, fat and energy estimated by bioelectrical impedance) at first AI did not influence the fertility rate at the first parturition, but did so at the second one (Taghouti et al, 2021). These authors reported that the increase in body protein and fat combined with a low body protein/energy ratio at first AI improved the fertility rate at the second parturition.…”
Section: Rearing Development and Body Statusmentioning
confidence: 80%